Changes in Green Space Use During a COVID-19 Lockdown Are Associated With Both Individual and Green Space Characteristics - Berdejo-Espinola, Violeta; Zahnow, Renee; Suárez-Castro, Andrés F.; Rhodes, Jonathan R.; Fuller, Richard A. (Frontiers in Ecology and Evolution, 2022)
Mobility restrictions imposed during the COVID-19 pandemic present a useful study system for understanding the temporal and spatial patterns of green space use. Here, we examine green space characteristics and sociodemographic factors associated with changes in frequency of green space use during a COVID-19 lockdown in Brisbane, Australia. We found that a large section of the population visited green spaces two to 11 times closer to their residences than the green space visited before lockdown. Differences between the distance from individuals’ residences to a green space before and during lockdown show dramatic individual decreases. Individuals who visited a different green space during lockdown than before tended to increase their frequency of visits (RRR = 1.188, p<0.01). In contrast, individuals who continued visiting their usual green space during lockdown were more inclined to decrease their number of visits (RRR=0.973, p<0.01). Use of green spaces was not only determined by their proximity or availability, but also by the presence of different access modes in the green spaces, such as carparks and/or public transport nodes. We found that males showed greater increases than females in the importance of green space for nature interactions and mental health benefits during the COVID-19 lockdown compared to before. More compact green spaces were associated with increased importance of urban green spaces for nature connections and social interactions while more irregularly shaped green spaces were associated with increased importance of urban green spaces for spiritual and family interactions. Our results provide key insights for future pandemic-resilient urban planning and policy.